Estimation of Ondansetron Hydrochloride in Pharmaceutical Dosage Forms by HPLC - Krishnaiah, Y.S.R.; Lakshmi, M.; Satyanarayana, V.; Bhaskar, P. (Asian Journal of Chemistry, 2010)
High pressure liquid chromatographic method (HPLC) has been developed for the estimation of ondansetron hydrochloride in its pharmaceutical tablet dosage forms using RP C-18 column. The mobile phase consisted of methanol and 0.02 M phosphate buffer in the ratio of 60 : 40 and doxazocin was used as internal standard. The detection was carried out at 213 nm and the linearity was found to be in the range of 0.01 to 59 μg/mL. The method is simple, precise, specific, less time consuming and accurate for the estimation of ondansetron hydrochloride in tablet dosage forms.